55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0350
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Development of a Multifunctional Hot Structure Heat Shield

Abstract: Development of a Multifunctional Hot StructureHeat Shield concept has initiated with the goal to provide advanced technology with significant benefits compared to the current state of the art heat shield technology. The concept is unique in integrating the function of the thermal protection system with the primary load carrying structural component. An advanced carbon-carbon material system has been evaluated for the load carrying structure, which will be utilized on the outer surface of the heat shield, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…7), results showed high local stresses in the ACC-6 material in the vicinity of the attachment points in the finite element model (FEM). These high stresses were occurring in the outer fibers of the T-beam stiffeners being modeled as beam elements, which were experiencing significant bending.…”
Section: A Critical Materials Property Testingmentioning
confidence: 97%
See 1 more Smart Citation
“…7), results showed high local stresses in the ACC-6 material in the vicinity of the attachment points in the finite element model (FEM). These high stresses were occurring in the outer fibers of the T-beam stiffeners being modeled as beam elements, which were experiencing significant bending.…”
Section: A Critical Materials Property Testingmentioning
confidence: 97%
“…Consequently, the preliminary development initiated with a focus on only the capsule heatshield, i.e., the heatshield without rigid deployable extensions, for an ISS return application. 7 This work included a trade study comparing the HOST concept to a traditional heatshield design. The initial results indicated that the HOST concept has the potential to save both mass and volume with significantly less recession compared to traditional heatshield designs.…”
Section: Introductionmentioning
confidence: 99%
“…PICA, which stands for Phenolic Impregnated Carbon Ablator, is composed of a porous carbon base and phenol-formaldehyde resin. However, studies conducted at NASA Langley research center [1] show that the use of carbon materials such as ACC-6, together with high porosity thermal insulation, makes it possible to create more weight-efficient designs. Ceramic matrix composites (CMC) reinforced with carbon fiber, despite their high oxidation-resistance and erosion-resistance and good mechanical characteristics, possess high density and thermal conductivity, which reduces their attraction as heat-shield materials.…”
Section: Introductionmentioning
confidence: 99%